Theoretical model and practical exploration of digital technology-empowered green management of water resource in semiconductor manufacturing industry - MA Beiling, AO Tong, ZHU Kangfu, LI Yonggang, HE Tianxiang (Ziyuan Kexue, 2023)
[Objective] This study focused on the green management of water resources in the semiconductor manufacturing industry based on digital technology. It analyzed the establishment of a comprehensive framework for green management of water resources from the perspective of technological empowerment, providing theoretical paradigm and practical guidance for the application of digital technology and the green development in the semiconductor manufacturing industry. [Methods] By systematically reviewing relevant literature on the domestic and international levels and incorporating multidisciplinary solutions, an innovative circular economy model was constructed. The article established a water resource green intelligent management system for semiconductor manufacturing enterprises, and used a case study method to select a typical semiconductor manufacturing enterprise, then deeply analyzed the application process of the technological framework. [Results] (1) Based on the “reduction, reuse, recycle” 3R principle of the circular economy model, and utilized the systematic analysis method, a theoretical model for the digital technology-empowered green management of water resources framework was built. (2) The theoretical model explained the connotation, characteristics, and functions of digital technology empowerment from the source to the end of each production process. It analyzed the specific measures of each enterprise under the 3R principle, and revealed the action path of data technology in empowering green management of water resources. (3) Through a case study of a semiconductor company in East China, the practical exploration of intelligent water resources green management technology solutions was achieved. The trend of data change over the past three years indicated a basic positive correlation between digital technology innovation and the benefits of green management of water resources, with higher benefits corresponding to higher innovation levels. [Conclusion] Digital technology can provide innovative green water resources management solutions for semiconductor manufacturing companies, enhancing their competitiveness. For the new development stage of the Chinese semiconductor manufacturing industry, it has significant implications for strengthening the dominant position of digital technology innovation and improving intelligent green management of water resources.